Errata: Communications - Scientific Letters of the University of Zilina, Vol. 20, No. 3, 2018, ``Electrochemical Characterization of Az31 Magnesium Alloy Treated by Ultrasonic Impact Peening (Uip)'', pp. 24-29. The proper Acknowledgement should be as follow - Kajanek, Daniel; Hadzima, Branislav; Pastorek, Filip (Communications - Scientific Letters of the University of Zilina, 2019)
Errata: Communications - Scientific Letters of the University of Zilina, Vol. 20, No. 3, 2018, ``Electrochemical Characterization of Az31 Magnesium Alloy Treated by Ultrasonic Impact Peening (Uip)'', pp. 24-29. The proper Acknowledgement should be as follows:The research was supported by project ITMS 26220220048 and by Slovak Research and Development Agency by the project No. APVV-14-0772.
Keywords: Errata: Communications - Scientific Letters of the University of Zilina; Vol. 20; No. 3; 2018; ``Electrochemical Characterization of Az31 Magnesium Alloy Treated by Ultrasonic Impact Peening (Uip)''; pp. 24-29. The proper Acknowledgement should be as follows: The research was supported by project ITMS 26220220048 and by Slovak Research and Development Agency by the project No. APVV-14-0772.